A Two-Dimensional Mathematical Model of Carbon Dioxide (CO2) Transport in Concrete Carbonation Proses - Muhammad Nur -Hidayat; Jeffry Kusuma; Naimah Aris (Jurnal Matematika, Statistika dan Komputasi, 2021)
A new two-dimensional mathematical model was developed to describe the transport phenomena of carbon dioxide in concrete structures. By treating transport phenomena as a concrete carbonation process, a two-dimensional linear partial differential equation was derived based on the principle of mass balance and convective-dispersive Equation. It was found the analytical solution by the separation of variables method combined with some substitution approaches. The numerical results are presented to illustrate the practical application of this model.